STUDY OF TYROSINASE INHIBITORY ACTIVITY AND PHYTOCHEMICAL SCREENING OF CASSIA FISTULA L. LEAVES - Wijaya, Caroline; Elya, Berna; Yanuar, Arry (International Journal of Applied Pharmaceutics, 2018)
Objective: This study was carried out to evaluate the phytochemical constituents and tyrosinase inhibitory activity of Cassia fistula leaves. Methods: A tyrosinase inhibitory activity assay was performed by measuring the decrease in the intensity of color suggestive of the inhibition of dopachrome formation resulting from the L-DOPA-tyrosinase reaction. Results: The test results showed that the tyrosinase inhibitory activity of the water fraction of C. fistula leaf extract had the highest IC50 value (152.031 Î¼g/mL) among other fractions (n-hexane, ethyl acetate, and n-butanol). An enzyme kinetic assay showed that the water fraction of C. fistula leaf extract inhibited tyrosinase with mixed-type inhibition. Phytochemical screening showed that the water fraction of C. fistula leaf extract contained alkaloids, flavonoids, glycosides, phenols, and tannins. Conclusion: The current study indicated that C. fistula leaves possess significant tyrosinase inhibitory activity.